Jung's views on causes and treatments of schizophrenia in light of current trends in cognitive neuroscience and psychotherapy research I. Aetiology and phenomenology. Issue 1 (27th January 2014) - Silverstein, Steven M.
Abstract: Jung's writings on schizophrenia are almost completely ignored or forgotten today. The purpose of this paper, along with a follow‐up article, is to review the primary themes found in Jung's writings on schizophrenia, and to assess the validity of his theories about the disorder in light of our current knowledge base in the fields of psychopathology, cognitive neuroscience and psychotherapy research. In this article, five themes related to the aetiology and phenomenology of schizophrenia from Jung's writings are discussed:1) abaissement du niveau mental ; 2) the complex; 3) mandala imagery; 4) constellation of archetypes and 5) psychological versus toxic aetiology. Reviews of the above areas suggest three conclusions. First, in many ways, Jung's ideas on schizophrenia anticipated much current thinking and data about the disorder. Second, with the recent (re)convergence of psychological and biological approaches to understanding and treating schizophrenia, the pioneering ideas of Jung regarding the importance of both factors and their interaction remain a useful and rich, but still underutilized resource. Finally, a more concerted effort to understand and evaluate the validity of Jung's concepts in terms of evidence from neuroscience could lead both to important advances in analytical psychology and to developments in therapeutic approaches that would extend beyond the treatment of schizophrenia.